Impact of Scalar Leptoquarks on Heavy Baryonic Decays. (9th October 2017) - Azizi, K.; Olgun, A. T.; Tavukoğlu, Z.
Abstract : We present a study on the impact of scalar leptoquarks on the semileptonic decays of Λ b, Σ b, and Ξ b . To this end, we calculate the differential branching ratio and lepton forward-backward asymmetry defining the processes Λ b → Λ l + l -, Σ b → Σ l + l -, and Ξ b → Ξ l + l -, with l being μ or τ, using the form factors calculated via light cone QCD in full theory. In calculations, the errors of form factors are taken into account. We compare the results obtained in leptoquark model with those of the standard model as well as the existing lattice QCD predictions and experimental data.